Obesity screening in the pediatric emergency department – A missed opportunity?. Issue 12 (December 2022) - Friedman, Nir; Erez-Granat, Ortal; Inbar, Alon; Dubnov-Raz, Gal
Abstract: Objectives: There is a low rate of body mass index measurements and obesity screening in primary pediatric care. Pediatric emergency department (PED) visits, with their large volumes and routine weight measurements, provide a unique opportunity to identify and address obesity. The study objectives were to examine the rate of addressing obesity in the PED and to identify its predicting factors. Methods: From electronic medical records of PED visits during 2010–2019, we extracted data on age, gender, weight, time, listed diagnoses, and discharge texts. The primary outcome was a listed diagnosis of "obesity" on discharge letters of children with obesity. Secondary outcomes were addressing weight in the discharge letter and written recommendations for obesity-related treatment. Mixed models were used to test for associations between each of the three outcomes and patient/visit characteristics. Results: There were 150, 250 PED visits by 88, 253 different children and adolescents. Obesity was found in 10, 691 children (12.1%). Among these, listed "obesity" diagnosis was present in only 240 (1.5%) visits. Text addressing overweight/obesity was recorded in 721 (4.4%) visits, and weight-related recommendations were documented in 716 (4.4%) visits. "Obesity" was documented in females more often than in males, in older children, in children with higher weights, and in visits conducted during the mornings. Conclusions: The rate of obesity diagnosis in the PED was extremely low, hence the potential screening ability of the PED in this matter is highly under-utilized. PEDs could increase the recognition of obesity, thus assisting in the global efforts in tackling this disease. Highlights: There is a low rate of pediatric obesity screening in primary care. Pediatric emergency department (PED) visits are an excellent opportunity to identify children with obesity. Parents can be highly receptive to obesity screening and treatment referrals in the setting of the PED. A very low rate of addressing and documenting weight status was found in charts of children with obesity who visited the PED. The potential ability of the PED to address obesity in children is highly underutilized. Abstract : Documentation; Pediatric emergency department; Obesity; Screening.